Transmisi Pesan dan Pemrosesan Informasi Individu Menyoal Diskriminasi di Indonesia dari Perspektif Van Kaam - Magfirah Magfirah; Rizky Saputra (President University, 2021)
AbstractThis study aims to describe the experience of individuals processing information and interpret the phenomenon of discrimination in Indonesia. This study uses the interpretive paradigm and the phenomenological tradition as a basis for theoretical thinking to understand the subjective world of communicators through in-depth interview instruments. Information Integration Theory is used to explain the process of forming cognitive structures and individual attitudes when interacting with discriminatory information obtained through a number of information media. The data analysis technique used the phenomenological approach proposed by Van Kaam. The results of this study indicate that information on discrimination cases appears in the daily activities of individuals accessing and using information, thus encouraging information processing in the individual's cognitive system. However, only a number of cases have been noticed and followed by individuals, such as cases of discrimination against ethnic Madurese in Kalimantan, Ahmadiyah congregations, students from Papua in Malang and Surabaya, and the Natalius Pigai case. Discrimination messages are transmitted via Facebook, Twitter, media coverage, research journals, and word of mouth. The phenomenon of discrimination in Indonesia is understood by individuals into three different meanings. Keywords: discrimination, phenomenology, Natalius Pigai, information processing, message transmission AbstrakPenelitian ini bertujuan untuk mendeskripsikan pengalaman individu memproses informasi dan memaknai fenomena diskriminasi di Indonesia. Penelitian ini menggunakan paradigma interpretif dan tradisi fenomenologi sebagai landasan berpikir teoritik untuk memahami dunia komunikator yang bersifat subyektif melalui intrumen wawancara mendalam. Teori Integrasi Informasi digunakan untuk menjelaskan proses terbentuknya struktur kognitif dan sikap individu ketika berinteraksi dengan informasi diskriminasi yang diperoleh melalui sejumlah media informasi. Teknik analisis data menggunakan pendekatan fenomenologi yang diusulkan oleh Van Kaam. Hasil penelitian ini menunjukkan bahwa informasi kasus diskriminasi muncul dalam aktivitas sehari-hari individu mengakses dan menggunakan informasi, sehingga mendorong terjadinya pemrosesan informasi di dalam sistem kognitif individu. Namun demikian, hanya sebagian kasus yang diperhatikan dan diikuti perkembangannya oleh individu seperti kasus diskriminasi warga etnis Madura di Kalimantan, jemaat Ahmadiyah, mahasiswa Papua di Malang dan Surabaya, serta kasus Natalius Pigai. Pesan diskriminasi ditransmisikan melalui Facebook, Twitter, pemberitaan media, jurnal penelitian, dan word of mouth. Fenomena diskriminasi di Indonesia, dipahami individu ke dalam tiga makna yang bervariasi. Kata kunci : diskriminasi, fenomenologi, Natalius Pigai, pemrosesan informasi, transmisi pesan